Transfer and contact-induced variation in child Basque - Austin, Jennifer (Frontiers in Psychology, 2015)
Young Basque-speaking children produce Differential Object Marking (DOM) and pre-verbal complementizers in their speech, variants argued to stem from contact with Spanish (Austin, 2006, Rodríguez-Ordóñez, 2013). In this paper, I claim that despite their contact-induced origin, these forms reflect distinct developmental tendencies on the part of the child acquiring Basque. Children's use of pre-verbal complementizers in Basque seems to be a relief strategy that bilingual children employ until they have acquired the post-verbal complementizers in Basque, which are low-frequency morphemes. In contrast, the use of DOM is present in the adult input, although children use this construction to a greater extent than adults do. Finally, I discuss the implications of these findings for the part that child learners play in advancing language change.